2020
DOI: 10.1039/d0ra03086d
|View full text |Cite
|
Sign up to set email alerts
|

Recent application of visible-light induced radicals in C–S bond formation

Abstract: The sulphur centered radicals, produced from various organic compounds, in high efficiency by single-electron-transfer (SET) oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…To construct the CÀ S bond, photoredox catalysis has caught a great attraction in the past few years due to its simple operation, mild conditions, and exclusion of stoichiometric oxidants. [89] In this context, Wang, Tu, Jiang, and co-workers in 2017, reported an Eosin-Y photocatalyzed arylsulfonylation and bicyclization of 1,7-enynes 125 with sulfinic acids 104 and obtained the corresponding benzo[a]fluoren-5-ones 126 in moderate to good yields (Scheme 39). [90] The optimized conditions revealed that the combination of Eosin-Y as a photocatalyst with K 2 CO 3 as a base delivered the best results.…”
Section: S-centered Radical Additionmentioning
confidence: 99%
“…To construct the CÀ S bond, photoredox catalysis has caught a great attraction in the past few years due to its simple operation, mild conditions, and exclusion of stoichiometric oxidants. [89] In this context, Wang, Tu, Jiang, and co-workers in 2017, reported an Eosin-Y photocatalyzed arylsulfonylation and bicyclization of 1,7-enynes 125 with sulfinic acids 104 and obtained the corresponding benzo[a]fluoren-5-ones 126 in moderate to good yields (Scheme 39). [90] The optimized conditions revealed that the combination of Eosin-Y as a photocatalyst with K 2 CO 3 as a base delivered the best results.…”
Section: S-centered Radical Additionmentioning
confidence: 99%
“…4 Regulations involving the lowering of the sulfur content in hydrocarbon fuels is very important as their burning can lead to emission of sulfur compounds into the atmosphere, causing problems for the environment and human health. 16,17 Conventional methods involving removal of sulfides such as organic solvent absorption, activated carbon adsorption, thermal incineration and catalytic combustion lead to complicated procedures, expensive secondary treatment with the risks of second pollution, fire, hazards and explosion accidents. [18][19][20] Electrochemical desulfurization (ECDS) involving oxidation of sulphur molecules is very simple and economic.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CÀ S cross-coupling reactions catalyzed by heterogeneous catalysts, ligand assisted catalysts, supported catalysts and photocatalysts, were compressively reviewed. [1,10,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Thus, in this review we have summarized the most recent examples of CÀ S cross coupling catalyzed by well-defined Cu and Ni complexes.…”
Section: Introductionmentioning
confidence: 99%